Effects of fermented Arctium lappa L. root by Lactobacillus casei on hyperlipidemic mice - MingJu Chen; Yuxiao Wu; Hongxuan Yang; Tianfeng Liu; Tongkun Han; Wangqiang Dai; Junyue Cen; Fan Ouyang; Jingjing Chen; Jianxin Liu; Lin Zhou; Xuguang Hu (Frontiers Media S.A., 2024)
IntroductionThis study aimed to establish a fermentation system based on Lactobacillus casei (LC) and Arctium lappa L. root (AR) to investigate its effects. The objectives included comparing metabolite profiles pre- and post-fermentation using untargeted metabolomics and evaluating the impact of LC-AR in high-fat diet-induced hyperlipidemic mice.MethodsUntargeted metabolomics was used to analyze differences in metabolites before and after fermentation. In vitro antioxidant activity, liver injury, lipid levels, pro-inflammatory cytokine levels, and cholesterol-related mRNA expression were assessed. 16S rRNA sequencing was conducted to evaluate changes in gut microbiota composition.ResultsLC-AR exhibited stronger antioxidant activity and higher metabolite levels than AR. It also improved liver injury as well as better regulation of lipid levels, pro-inflammatory cytokine levels, and cholesterol-related mRNA. 16S rRNA analysis revealed that LC-AR decreased the Firmicutes/Bacteroidetes ratio, which correlated negatively with triglycerides, total cholesterol, and low-density lipoprotein cholesterol levels.DiscussionThese findings suggest that LC-AR may serve as a promising functional food and drug raw material for improving hyperlipidemia, particularly through its beneficial effects on gut microbiota and lipid regulation.